The Interplay Between Biliary Occlusion and Liver Regeneration: Repeated Regeneration Stimuli Restore Biliary Drainage by Promoting Hepatobiliary Remodeling in a Rat Model - Richter, Beate; Sänger, Constanze; Mussbach, Franziska; Scheuerlein, Hubert; Settmacher, Utz; Dahmen, Uta (Frontiers in Surgery, 2022)
Background: Patients with malignant biliary obstruction do not seem to benefit from “two-stage hepatectomy” due to an impairment of liver regeneration. We used the “two-stage hepatectomy” model in rats to investigate (1) the impact of preexistent cholestasis of different extent on the time course of liver regeneration and (2) the dynamics of hepatobiliary remodelling under regeneration conditions. Materials and Methods: We used rats for a sequence of 3 operations: induction of biliary occlusion, followed by a “two-stage hepatectomy” with portal vein ligation (70% of the liver volume, sPVL) as first stage and a 70%-hepatectomy (70%PHx) as second stage. We induced biliary occlusion of different extents: 100% of liver, tBDT or 70%, sBDT or 0%, Sham. The first experiment (n=45 rats) investigated liver regeneration, proliferative activity and hepatobiliary histomorphology (2D-histology: HE, BrdU) in the future liver remnant (FLR). The second experiment (n=25 rats) explored the dynamics of hepatobiliary remodelling with different regenerative pressure using µCT scan. Results: tBDT led to a 2.4-fold increase in whole liver volume due to severe biliary proliferation within 14 days. sBDT caused only a minor volume gain (1.7-fold). sPVL caused substantial volume gain of FLR (tBDT: 3-fold; sBDT: 2.8-fold; Sham 2.8-fold) and a substantial atrophie of the portally ligated lobes (tBDT: 0.9-fold; sBDT: 0.6-fold; Sham: 0.4-fold). 70%PHx promoted a further volume gain of FLR (tBDT: 4-fold; sBDT: 3-fold; Sham 3-fold) until POD 28. tBDT led to biliary proliferates, replacing ~15% of the hepatocellular tissue. After sPVL and even more after 70%PHx we found a reduction of the biliary proliferates, finally resulting in an almost complete recovery of the hepatocellular tissue in the FLR. After sBDT and Sham we observed a normal liver morphology in the FLR at all time points. CT-scans visualized extrahepatic biliary collaterals in most of the animals after two stimuli (60%, 3/5). Histological workup identified typical biliary epithelium. Conclusion: Liver volume of FLR increased in tBDT due to biliary proliferates. Repeated regeneration stimuli promoted almost full restoration of hepatocellular architecture in FLR by re-establishing biliary drainage via formation of biliary collaterals. This model can help exploring the dynamics in hepatobiliary remodelling in cholestasis.